Peningkatan Kreativitas Guru dalam Program School in the Park Melalui Metode Group-Based Flipped Classroom - Isaeni, Nita (Jurnal Didaktika Pendidikan Dasar, 2022)
The increase in teacher creativity in strengthening the value of students' entrepreneurial character can be seen from the planning, implementation and assessment of learning. The research was conducted on students at SMPN 4 Lembang, West Bandung Regency in the School in the Park program. This program utilizes the geographical wealth of the school environment as a learning resource in applying character values ​​(entrepreneurship) which is integrated in the development of teaching tools by teachers and also in the preparation of school programs related to the importance of life skills for students. By using the Group based-Flipped Classroom method, intervention activities were carried out to 10 subject teachers online. Activities are divided into three, namely pre-meeting, meeting and post-meeting. At the pre-meeting, assignments were given to teachers related to the use of the Merdeka Mengajar Platform. Qualitative descriptive research was carried out in even semesters using instruments such as observation sheets, interviews and analytical documents. The results of the analysis of the data indicate that the increase in teacher creativity in implementing integrated entrepreneurial values ​​in subjects including Mathematics, Language, Cultural Arts is illustrated in teaching tools where the selection of themes, management of learning activities, assignments and assessments are character-based. On the other hand, changes in student attitudes can be seen from the achievement of the attitude values ​​of each class.